Improving Students’ Ability to Write Poems Through Scientific Discovery-Based Learning with Nature Pictures from Media - Rahayu, E; Rohmadi, M; ., Andayani (KnE Social Sciences, 2018)
This study aimed: 1) to increase the interest in writing poems; and 2) to improve the ability to write poetry among students in grade VIII. This research was a classroom action research and was conducted between August and November 2016 in class VIII at SMP in Sukoharjo. The techniques used for data collection were observation, in-depth interviews, tests, and document analysis. From the results, it can be concluded that there is an improvement in the students’ interest in writing poetry that shown by the fact: 1) in the first cycle, 24 students or 47% joined the teaching and learning process, and this increased to 75% of the students in the second cycle; 2) in the first cycle, writing skills increased to 81% (26 students), which became 96% (31 students) in the second cycle. Keywords: discovery-based learning, scientific method, writing poem ability